2023
DOI: 10.1039/d3qi00138e
|View full text |Cite
|
Sign up to set email alerts
|

Dual-cation doping precisely reducing the energy barrier of the rate-determining step for promoting oxygen-evolving activity

Abstract: The energy barrier for the rate-determining step (RDS) is exceptionally critical for the catalytic oxygen evolution reaction (OER) efficiency of an electrocatalyst; however, facilely decreasing the energy barrier of RDS...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…After a thorough study, it is revealed that the superb electrocatalytic performance is stemmed from the enlarged ECSA after NH 3 ·H 2 O etching, which can thus expose more catalytically active sites toward the electrooxidation reactions. More significantly, XPS analysis also revealed that the NH 3 ·H 2 O etching can create a higher concentration of high oxidation states of metals, which can serve as active species toward electrooxidation reactions. , Furthermore, the strong synergistic effect evolved from the multielement active sites also contributes to the improved electrocatalytic performance. Upon combination of these advantages, HE-PBA-e can thus deliver superb electrocatalytic performance toward OER, EOR, and UOR.…”
Section: Resultsmentioning
confidence: 99%
“…After a thorough study, it is revealed that the superb electrocatalytic performance is stemmed from the enlarged ECSA after NH 3 ·H 2 O etching, which can thus expose more catalytically active sites toward the electrooxidation reactions. More significantly, XPS analysis also revealed that the NH 3 ·H 2 O etching can create a higher concentration of high oxidation states of metals, which can serve as active species toward electrooxidation reactions. , Furthermore, the strong synergistic effect evolved from the multielement active sites also contributes to the improved electrocatalytic performance. Upon combination of these advantages, HE-PBA-e can thus deliver superb electrocatalytic performance toward OER, EOR, and UOR.…”
Section: Resultsmentioning
confidence: 99%
“…The downshi of E d can also be clearly observed in PdRu-RuO 2 compared to that of the PdRu alloy, which reveals that the formation of the heterostructure can optimize the binding strength with the intermediates and contribute to the enhanced catalytic performance. 46,47 The XPS demonstrated that the DF between PdRu and RuO 2 was decreased from 0.37 eV to 0.03 eV aer the formation of the PdRu alloy and abundant oxygen vacancies in the RuO 2 (Table S1 †).…”
Section: Resultsmentioning
confidence: 99%
“…41,42 From the perspective of electrochemical reactions, atomic structure engineering can induce additional active sites, create surface defects, and modify the adsorption capability with intermediates. [43][44][45][46] For instance, Fan et al 47 reported the synthesis of efficient 2D bimetallene PdRh hydride catalysts, in which the H atoms could stabilize the PdRh bimetallene. Detailed synthesis procedures indicated that the RhPd-H bimetallenes were existed because of the introduction of H that in situ chemically released from the formaldehyde solution during the synthesis process.…”
Section: Nonmetal Dopingmentioning
confidence: 99%